Effect of Transplanting Dates, Cultivars and Irrigation Regimes on Microclimate and Yield of Rice - Saha, Salil; Mukherjee, Asis; Banerjee, Saon (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted at BCKV, Kalyani, West Bengal (Latitude 22°59’13’’ N, Longitude 88°27’20’’ E) to evaluate the performance of different rice cultivars grown during kharif season of 2017. The experiment was laid down in a split split-plot design where four dates of transplanting (16th June, 30th June, 14th July and 28th July) were allotted in main plot, three rice cultivars (Nayanmani, Satabdi, Swarna) in sub-plot and two irrigation regimes (Optimum and Deficit) in sub-sub plot. Result revealed that the grain yield (4365 kg ha-1) was recorded in 16th June transplanting, highest which significantly declined by 15%, 31% and 36% respectively with delay in transplanting. Deficit irrigation resulted 851 kg ha-1 less grain yield compare to optimum irrigation condition (3915 kg ha-1). Grain yield under different variety was in the order of Nayanmani (4495 kg ha-1) > Swarna (3008 kg ha-1)>Satabdi (2965 kg ha-1).The highest magnitude (0.98 g MJ-1) of radiation use efficiency was noted under D1, which decrease gradually with delay in transplanting time (0.79 g MJ-1>0.64 g MJ-1>0.58 g MJ-1). The highest magnitude (0.87 g MJ-1) of RUE was noted under optimum irrigation, which was 0.15 g MJ-1 less under deficit irrigation. Among the varieties, the highest magnitude (1.10 g MJ-1) of RUE was recorded under Nayanmani, which was 0.40 g MJ-1 less under Satabdi. The lowest RUE (0.48 g MJ-1) was noted under Swarna.